DAMPAK MATA KULIAH PENDIDIKAN KONSUMEN TERHADAP PERUBAHAN PERILAKU KONSUMEN PADA MAHASISWA TATA RIAS UNIVERSITAS NEGERI SURABAYA - oktavia Ronita, shella; Ayu Vidiana Syafitri; Grace Kaleka; Laurent Nemta Zula Latmafanie (Universitas Negeri Surabaya, 2023)
Humans have the desire to own or consume goods in excess or the goods consumed are usually less necessary and are not classified as basic needs. Even though consumers should be able to act rationally in meeting their needs, the fact is that there are not a few consumers who behave irrationally or fulfill their desires by buying only the goods they want. This study uses a qualitative method. The results obtained are a real illustration of changes in the behavior of Cosmetology children who have taken Consumer Education courses. This research data collection technique uses: Questionnaire.Based on the results of data analysis, it can be concluded that: it can be seen that many students are more concerned with shopping according to their wishes, not according to their life needs before receiving consumer education knowledge. Cosmetology students, the majority of whom are women, tend to choose items based solely on their interests, such as attractive colors or unique shapes, so that they do not get the good function of the items purchased. After getting to know consumer education, cosmetology students prefer to shop according to their needs and be careful in buying goods so they don't get scammed. Therefore courses are very important for teaching how to prioritize needs before consuming something, a priority scale is a scale that shows what goods or services are most important and must be purchased first.